Breast spindle cell tumours: about eight cases - Abd El All Howayda S (BMC, 2006)
Abstract Background Breast spindle cell tumours (BSCTs), although rare, represent a heterogeneous group with different treatment modalities. This work was undertaken to evaluate the utility of fine needle aspiration cytology (FNAC), histopathology and immunohistochemistry (IHC) in differentiating BSCTs. Methods FNAC of eight breast masses diagnosed cytologically as BSCTs was followed by wide excision biopsy. IHC using a panel of antibodies against vimentin, pan-cytokeratin, s100, desmin, smooth muscle actin, CD34, and CD10 was evaluated to define their nature. Results FNAC defined the tumors as benign (n = 4), suspicious (n = 2) and malignant (n = 3), based on the cytopathological criteria of malignancy. Following wide excision biopsy, the tumors were reclassified into benign (n = 5) and malignant (n = 3). In the benign group, the diagnosis was raised histologically and confirmed by IHC for 3 cases (one spindle cell lipoma, one myofibroblastoma and one leiomyoma). For the remaining two cases, the diagnosis was set up after IHC (one fibromatosis and one spindle cell variant of adenomyoepithelioma). In the malignant group, a leiomyosarcoma was diagnosed histologically, while IHC was crucial to set up the diagnosis of one case of spindle cell carcinoma and one malignant myoepithelioma. Conclusion FNAC in BSCTs is an insufficient tool and should be followed by wide excision biopsy. The latter technique differentiate benign from malignant BSCTs and is able in 50% of the cases to set up the definite diagnosis. IHC is of value to define the nature of different benign lesions and is mandatory in the malignant ones for optimal treatment. Awareness of the different types of BSCTs prevents unnecessary extensive therapeutic regimes.